Diagnosing Business Incubation for Social Purpose: A Viable System Model Approach - Adham, KA; Muhamad, NS; Said, MF; Sarhadat, SA; Ismail, HA; Nasir, MFAM (Springer New York LLC, 2024)
Indexed by WOS/SCOPUS